A parametric sensitivity study on preforming simulations of woven composites using a hypoelastic computational model. (February 2016) - Khan, Muhammad A; Saleem, Waqas; Asad, Muhammad; Ijaz, Hassan
Preforming simulation for structural composite processing can significantly assist in the development of forming tools, prediction of manufacturing issues, optimization of process parameters and structural design analysis. The present study is aimed at investigating the influence of some important parameters in composite forming using a hypoelastic computational model developed for simulating the deformation behaviour of fibrous materials. The process parameters considered within this numerical work investigate the effects of binder force, coefficient of friction and forming speed. The study is conducted using two most commonly used double-curvature geometries for analysis of woven composites: double dome and hemisphere. It has been shown with this comprehensive study that the forming simulations are greatly affected by the choice of process parameters, and models based on finite element approach, such as the proposed hypoelastic model, can only predict its effects.